2014
DOI: 10.1111/are.12652
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of initial swim bladder inflation and effect of initial inflation failure on skeletal malformation in cultured seven-band grouperHyporthodus septemfasciatus(Thunberg)

Abstract: The effects of the removal of the oily surface film on initial swim bladder inflation and survival in cultured seven‐band grouper Hyporthodus septemfasciatus were investigated during the larval stage. Additionally, the relationship between swim bladder inflation failure and malformations in later stages was examined. To explore promotion conditions for inflation, duplicate experiments were conducted under three different water surface conditions: removal of the oily surface film (ROF group), covering the water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Previous studies on various species, including longtooth grouper, have correlated lordosis with lack of a functional swim bladder (Chatain, ; Hayashida et al, ; Jacquemond, ; Kitajima, ; Kitajima et al, ; Nagano et al, ; Tsuji et al, ; Uji, ), as observed in the present study. In those reports, the position of lordosis was mostly allocated to two regions: (a) at positions between the prehaemal and haemal vertebrae (such as found in red seabream (Kitajima, ; Kitajima, Iwamoto, & Matsukiyo, ), European seabass ( Dicentrarchus labrax ) and gilthead bream (Chatain, ) or (b) on the haemal vertebrae [such as found in black seabream ( Acanthopagrus schlegelii ; Kitajima, ), Japanese seabass ( Lateolabrax japonicus ; Hayashida et al, ) and Eurasian perch ( Perca fluviatilis ; Jacquemond, )].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Previous studies on various species, including longtooth grouper, have correlated lordosis with lack of a functional swim bladder (Chatain, ; Hayashida et al, ; Jacquemond, ; Kitajima, ; Kitajima et al, ; Nagano et al, ; Tsuji et al, ; Uji, ), as observed in the present study. In those reports, the position of lordosis was mostly allocated to two regions: (a) at positions between the prehaemal and haemal vertebrae (such as found in red seabream (Kitajima, ; Kitajima, Iwamoto, & Matsukiyo, ), European seabass ( Dicentrarchus labrax ) and gilthead bream (Chatain, ) or (b) on the haemal vertebrae [such as found in black seabream ( Acanthopagrus schlegelii ; Kitajima, ), Japanese seabass ( Lateolabrax japonicus ; Hayashida et al, ) and Eurasian perch ( Perca fluviatilis ; Jacquemond, )].…”
Section: Discussionsupporting
confidence: 85%
“…In those reports, the position of lordosis was mostly allocated to two regions: (a) at positions between the prehaemal and haemal vertebrae (such as found in red seabream (Kitajima, ; Kitajima, Iwamoto, & Matsukiyo, ), European seabass ( Dicentrarchus labrax ) and gilthead bream (Chatain, ) or (b) on the haemal vertebrae [such as found in black seabream ( Acanthopagrus schlegelii ; Kitajima, ), Japanese seabass ( Lateolabrax japonicus ; Hayashida et al, ) and Eurasian perch ( Perca fluviatilis ; Jacquemond, )]. However, two studies of sevenband grouper ( E. septemfasciatus ) differed in the reported position of lordosis: Nagano et al () found the condition at V8–11 (between the prehaemal and haemal vertebrae), whereas Tsuji et al () reported the condition at V15–18 (at the haemal vertebrae). This suggests that the position of lordosis may be influenced by various factors, including rearing conditions and swim bladder inflation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malformations decrease production efficiency in finfish aquaculture due to delayed growth, poor survival, disposal of malformed fish unsuitable for sale and a decline in the price of harvest. Vertebral anomalies are the major malformations in fish (Boglione et al, ; Fjelldal, Hansen, & Berg, ; Lewis‐McCrea & Lall, ; Tsuji et al, , etc. ), and it is beneficial to elucidate their causes and to establish preventive methods.…”
Section: Introductionmentioning
confidence: 99%